Navigating Perspectives: Unpacking the Discourse Surrounding International Student Experiences in Canadian Higher Education - Shamiga Arumuhathas (Canadian Society for Studies in Education, 2023)
The oscillation of Canadian international higher education policies continues to construct, re-frame, and re-contextualize how international students of colour are perceived by domestic institutional actors within Canadian higher education institutions. Through a preliminary textual and critical discourse analysis, this paper aims to navigate various discursive perspectives within existing literature to understand the broader and detrimental implications of framing international students through a deficit and problem-laden lens. The positional paper illuminates accounts of Canadian international students' culture shock and social integration, lack of support/resources in adjusting to their new academic environment, insufficient information provided by Canadian universities, and difficulties making new companions which ultimately hinders the student experience and academic outcomes. In discussing the apparent dissonance and discrepancies, this paper offers alternative solutions that perhaps mitigates international students' negative experiences and offer robust institutional resources, support, and services.